Development of Smart Apps Creator on Basic Tajweed Science Material in Islamic Religious Education Learning at Elementary School Level - Muchamad Indra Sudarmawan (Global Action and Education for Society, 2025)
Technological innovation is needed as a breakthrough effort to ensure the continuous development of learning. In Islamic Religious Education (PAI) learning, the Covid-19 pandemic has become a momentum for the use of interactive application media to improve learning effectiveness. One such application, the Smart Creator application, has proven to help facilitate the learning of Basic Tajweed in Islamic Religious Education (PAI) subjects at the elementary school level. This study applied research and development (R&D) methods to produce an interactive Basic Tajweed application. Data were collected through interviews and a questionnaire analyzing learning media needs. Media development was carried out using Smart App Creator because it is easy to use and able to integrate various learning support media. The results showed that the use of Smart App Creator interactive multimedia in Basic Tajweed material can increase student activity, creativity, and thinking skills, thus impacting improved learning outcomes. Students' understanding of basic Tajweed also showed a positive response. This media is considered interesting, easy to use, and has clear instructions, thus fostering learning interest until the end of the lesson. Therefore, this interactive multimedia is suitable for teachers to use as an innovative, varied, and not boring learning medium.